2020
DOI: 10.14738/assrj.73.7942
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of the WH-Questions in the EFL Textbook of That's Right

Abstract: In the current study, the researchers analyzed the units of the textbook "That's Right" for 10 th grade students for English teaching in Israel. The study examined the WHquestions found in the textbook according to the various cognitive levels of Bloom's Taxonomy. By using Bloom's taxonomy, the researchers attempted to understand whether WH-questions used in the textbook emphasize high-level thinking and cognitive skills development. The question of this study is: To what extent do the WHquestions in the textb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results showed that the distribution of Higher Order Thinking Skills in essay reading questions in the Pathway to English textbooks was low and unbalanced, because higher order thinking skills in the Pathway to English textbooks have fewer questions about reading essay practice questions, and less variation in Higher Order Thinking Skills. Igbaria and Ghanayem (2020) research results showed that 245 out of the 324 questions emphasized cognition levels that develop Lower Order Thinking Skills, while only 79 questions emphasized the three levels that use higher-order thinking Skills.…”
Section: Empirical Studies On Textbook Analysismentioning
confidence: 92%
“…The results showed that the distribution of Higher Order Thinking Skills in essay reading questions in the Pathway to English textbooks was low and unbalanced, because higher order thinking skills in the Pathway to English textbooks have fewer questions about reading essay practice questions, and less variation in Higher Order Thinking Skills. Igbaria and Ghanayem (2020) research results showed that 245 out of the 324 questions emphasized cognition levels that develop Lower Order Thinking Skills, while only 79 questions emphasized the three levels that use higher-order thinking Skills.…”
Section: Empirical Studies On Textbook Analysismentioning
confidence: 92%